PRA RANCANG BANGUN PABRIK PUPUK BIOCHAR DARI CANGKANG KEMIRI DENGAN KAPASITAS 6.450,9320 TON/TAHUN MENGGUNAKAN ALAT UTAMA ROTARY KILN - Ayu, Agnes Diah; Iskandar, Taufik (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2019)
Biochar fertilizer is a porous black charcoal produced by pyrolysis process with a relative temperature below 700 oC enriched with nitrogen (N). The benefits of biochar fertilizer are as a natural fertilizer (organic fertilizer) which is good for improving the condition of contaminated soil due to excessive use of chemical fertilizers and pesticides. Pecan shell waste has the potential to be used as a raw material in making biochar fertilizer by adding chicken manure which serves as a substitute for nitrogen elements that are lost in the candlenut biochar which is reduced or disappears during the pyrolysis process. The design of biochar fertilizer is planned to be established in 2021 in Dairi Regency, North Sumatra. Production capacity is planned to be 6,450.9320 tons / year with 9 hours / production, 300 days / year and in one day there are 2 processes. The process used is slow pyrolysis (slow pyrolysis) is one of the technologies used to convert hazelnut shell waste into charcoal (biochar). Based on economic analysis, the total investment in production is Rp. 15,924,053,007.45. Product sales value of Rp. 38,705,591,883 per year, with profit before and after tax is Rp. 9,978,936885 per year and Rp. 8,981,043,197 per year. The results of the feasibility analysis obtained ROI at (%): 64.86%, POT (Year): 1.4 Years, BEP (%): 32.333%, IRR (%): 20.296% So it can be concluded that the Pre-Design of Biochar Fertilizer with capacity of 6,450.9320 tons/year is worthy of being established.